Assistance in Financial Management and Digital Marketing for Village-Owned Enterprises (Bumdes) in Gunungkidul - Erniyati Caronge; Bruna Costa; Tiago Costa (Yayasan Adra Karima Hubbi, 2025)
Background. Village-Owned Enterprises (BUMDes) play a crucial role in promoting local economic development in rural Indonesia. However, many BUMDes face persistent challenges in financial management and digital marketing, which limit their growth and sustainability. These challenges are particularly evident in rural areas such as Gunungkidul District, Yogyakarta, where limited managerial capacity and digital literacy hinder enterprise development. Purpose. This study aims to examine the effectiveness of assistance and capacity-building programs in improving financial management and digital marketing competencies among BUMDes managers in Gunungkidul. Specifically, it seeks to assess how such support contributes to operational sustainability and expanded market reach. Method. The study employs a mixed-methods approach by combining quantitative surveys and qualitative interviews. Data were collected from managers of 15 BUMDes in Gunungkidul District, focusing on changes in financial performance and the adoption of digital marketing practices following participation in assistance programs. Results. The findings indicate that the training and assistance programs significantly improved financial management practices among BUMDes managers. In addition, there was a notable increase in the adoption of digital marketing strategies, which enhanced business visibility, customer reach, and overall financial sustainability of the participating BUMDes. Conclusion. The study concludes that targeted support in financial management and digital marketing is effective in strengthening the capacity and sustainability of BUMDes in Gunungkidul. These findings highlight the importance of structured capacity-building programs in empowering local enterprises and provide a practical model that can be replicated in other rural areas to enhance economic resilience and community-based development.